A dual-functional metamaterial for integrated vibration isolation and energy harvesting. (29th September 2021) - Lu, Ze-Qi; Zhao, Long; Ding, Hu; Chen, Li-Qun
Abstract: Enhancing vibration isolation with locally resonant metamaterials has attracted wide attention due to low-frequency band-gap. Moreover, nonlinear periodic structure could improve the range of targeted energy transfer. In this paper, we propose a dual-functional metamaterial for integrated low-frequency vibration isolation and energy harvesting. A periodic array of nonlinear electrical energy harvesters, realized by implanting a rolling-ball with coils into a spherical magnetic cavity, is explored to isolate mechanical wave and simultaneously harvest electrical energy. The dynamical equation is established for a nonlinear dual-functional metamaterial beam under transverse excitation. The Extended Bloch's theorem is applied to give the dispersion relation. Numerical results obtained by finite element method supported the analytical results. Compared to the narrow band-gaps in metamaterials with spherical magnetic cavity, our numerical analysis demonstrates that a cavity mass arrayed beam with a periodic array of nonlinear energy harvesters has more and wider low-frequency band-gaps. Frequency response functions of output power are derived by using finite element analysis. The harvested power is considerable at the local resonant band-gap. Parameter study demonstrates that increasing the cell size and increasing cavity mass could improve elastic waves isolation performance at low frequencies; Increasing the mass of the rolling-ball in the resonator can significantly decrease the frequency of the local resonance band-gap. The existence of multiple band-gaps could be designed for dual-functional vibration attenuation and energy harvesting. Finally, an experimental rig is designed to validate the theoretical results.